STABILITY OF MICROSPHERE OF SARGASSUM PLAGYOPHYLLUM (MERTENS) J. G. AGARDH EXTRACT PRODUCED BY SPRAY DRYING USING MALTODEXTRIN - Anwar, Effionora; Yulianti, Dyah Ayu Ratna; Putri, Kurnia Sari Setio (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to determine the stability of microspheres of Sargassum plagyophyllum (brown seaweed) after preparation using spray drying with maltodextrin DE 10–15 and during drying and storage. Methods: Aqueous extracts of brown seaweed were formulated into microspheres using maltodextrin DE 10–15 as a coating agent. For increasing the stability of polyphenol compounds, spray drying was performed with an inlet temperature of 110°C. Four microsphere formulations were produced using maltodextrin DE 10–15 at concentrations of 0%, 5%, 10%, and 15%. The resulting microspheres were then characterized in the assessments of moisture contents, particle size distributions, pH, total phlorotannin contents, and antioxidant activity, and surface morphology was analyzed using scanning electron microscope analyses. Results: Powders that were produced with 0% and 15% maltodextrin were more stable at 4°C±2°C than at 28°C±2°C and 40°C±2°C. At the lowest temperature, phlorotannin contents were maintained in powders that were prepared with 15% maltodextrin but were decreased by 10% in powders that were prepared without maltodextrin. Conclusion: Maltodextrin DE 10–15 is a suitable coating agent for dry formulations of S. plagyophyllum powder and maintained stability during spray drying at 110°C and during storage for 2 months at 4°C±2°C.